2018
DOI: 10.3390/su10061871
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Enterprises Radical Innovation and Performance: Insights into Strategic Orientation of Cultural and Creative Enterprises

Abstract: A firm's strategic orientation determine its business direction and scope of operation. Several researchers have tried to identify how strategic orientations affect business development. However, only a few scholars have explored how strategic orientations shape a firm's organizational capability. In addition, the extent to which radical innovation contributes to a firm's operations has not been well researched. Given these research shortcomings, this study explores the integration of firms' strategic orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 80 publications
2
32
0
3
Order By: Relevance
“…Research on the success of enterprises includes theoretical and empirical studies on the organizational behaviors, strategic planning, and resource competitiveness (Barney, 1991;Grant, 2016;Shih, 2018) of firms across many different commercial markets and industries. When exploring the reasons why firms participate in trade shows, researchers focus on two distinct perspectives: selling and non-selling.…”
Section: Theory Base and Participatory Perspectives At Trade Showsmentioning
confidence: 99%
See 3 more Smart Citations
“…Research on the success of enterprises includes theoretical and empirical studies on the organizational behaviors, strategic planning, and resource competitiveness (Barney, 1991;Grant, 2016;Shih, 2018) of firms across many different commercial markets and industries. When exploring the reasons why firms participate in trade shows, researchers focus on two distinct perspectives: selling and non-selling.…”
Section: Theory Base and Participatory Perspectives At Trade Showsmentioning
confidence: 99%
“…According to researchers in the resource-based view, strategy theory, and competitive advantages, intangible resources may include: reputation, relationships (Arnett & Madhavaram, 2012), innovation (Antoldi, Cerrato, & Depperu, 2013), or organizational culture (Shih, 2017), all of which are difficult to imitate. The importance of intangible resources for a firm's successful internationalization has been also explored (Lages et al, 2009;Hongchindaket, Kittisarn, & Neck, 2013;Grant, 2016;Shih, 2017Shih, , 2018. The following sections provide detailed discussions.…”
Section: Theory Base and Participatory Perspectives At Trade Showsmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout their study, they found that perceived usefulness (PU) and perceived ease of use (PEOU) are observed to be the key factors affecting BI. Shih [30] did a study to identify the determinants of different factors: enterprises' strategic orientations, competitive advantages, radical innovation and business performance with a sample of 86 firms via regression analysis using the PLS SEM model. This study concluded that a firm's radical innovation capability and adoption can be enhanced through either market orientation factor or entrepreneurial orientation factor, while brand advantage has a significant impact on firms' performance.…”
mentioning
confidence: 99%